The First Chemically-Synthesised, Highly Immunogenic Anti-SARS-CoV-2 Peptides in DNA Genotyped Aotus Monkeys for Human Use - Patarroyo, Manuel E.; Patarroyo, Manuel A.; Alba, Martha P.; Pabon, Laura; Rugeles, María T.; Aguilar-Jimenez, Wbeimar; Florez, Lizdany; Bermudez, Adriana; Rout, Ashok K.; Griesinger, Christian; Suarez, Carlos F.; Aza-Conde, Jorge; et al. (Frontiers in Immunology, 2021)
Thirty-five peptides selected from functionally-relevant SARS-CoV-2 spike (S), membrane (M), and envelope (E) proteins were suitably modified for immunising MHC class II (MHCII) DNA-genotyped Aotus monkeys matched with HLA-DRβ1* molecules for use in humans, aimed at producing the first minimal subunit-based, chemically-synthesised, immunogenic molecules (COLSARSPROT) covering several HLA alleles. As they induced very high immunofluorescent antibody (IFA) and ELISA titres against S, M and E parental peptides and neutralising antibodies (NAb), they were predicted to cover 48.25% of the world’s population for 6 weeks (short-term) and 33.65% for 15 weeks (long-lasting), simultaneously 30 serum samples from individuals recovered from relatively mild and 3D structural analysis (by 600-900 MHz 1H-NMR) suggested structural-functional immunological association. This data highlights such chemically synthesis methodology’s potential for obtaining pure, highly reproducible, stable, cheap, easily-modifiable peptides for immune protection induction against COVID-19, covering a considerable amount of the human population. Severe SARS-CoV-2 infections were analysed for antigenicity with the same immunological methods that allowed us the identification of new peptides to include in COLSARSPROT mixture, increasing the potential coverage of these chemically synthesized peptides.